Dual Role and Product Featuring Strategy of Digital Platform - Wang, Ruitong; Qiu, Ye (Marketing Science, 2024)
This paper examines the ramification of the platform’s dual role on its featuring strategy, sellers’ pricing strategies, and consumer welfare.